Impact of 6-Month Exposure to Aerosols From Potential Modified Risk Tobacco Products Relative to Cigarette Smoke on the Rodent Gastrointestinal Tract - Battey, James N. D.; Szostak, Justyna; Phillips, Blaine; Teng, Charles; Tung, Ching Keong; Lim, Wei Ting; Yeo, Ying Shan; Ouadi, Sonia; Baumer, Karine; Thomas, Jerome; Martinis, Jacopo; Sierro, Nicolas; et al. (Frontiers in Microbiology, 2021)
Cigarette smoking causes adverse health effects that might occur shortly after smoking initiation and lead to the development of inflammation and cardiorespiratory disease. Emerging studies have demonstrated the role of the intestinal microbiome in disease pathogenesis. The intestinal microbiome is susceptible to the influence of environmental factors such as smoking, and recent studies have indicated microbiome changes in smokers. Candidate modified risk tobacco products (CMRTP) are being developed to provide substitute products to lower smoking-related health risks in smokers who are unable or unwilling to quit. In this study, the ApoE-/- mouse model was used to investigate the impact of cigarette smoke (CS) from the reference cigarette 3R4F and aerosols from two CMRTPs based on the heat-not-burn principle (carbon-heated tobacco product 1.2 [CHTP 1.2] and tobacco heating system 2.2 [THS 2.2]) on the intestinal microbiome over a 6-month period. The effect of cessation or switching to CHTP 1.2 after 3 months of CS exposure was also assessed. Next-generation sequencing was used to evaluate the impact of CMRTP aerosols in comparison to CS on microbiome composition and gene expression in the digestive tract of mice. Our analyses highlighted significant gene dysregulation in response to 3R4F exposure at 4 and 6 months. The findings showed an increase in the abundance of Akkermansiaceae upon CS exposure, which was reversed upon cessation. Cessation resulted in a significant decrease in Akkemansiaceae abundance, whereas switching to CHTP 1.2 resulted in an increase in Lactobacillaceae abundance. These microbial changes could be important for understanding the effect of CS on gut function and its relevance to disease pathogenesis via the microbiome.